EP130/#1060 Treatment patterns for leiomyosarcomas, endometrial stromal sarcomas and adenosarcomas: a national cancer database study. (4th December 2022) - Kunzman, Jessica; Hutten, Ryan; Kelley, Kristen; Harris, Kate; Gaffney, David; Decesaris, Cristina; Suneja, Gita; Burt, Lindsay
Abstract : Objectives: Uterine sarcomas are a rare, heterogenous, group of cancers with limited data on optimal adjuvant treatment. We examined patterns of care for leiomyosarcomas, endometrial stromal sarcomas (ESS), adenosarcomas, and mixed uterine sarcomas using the National Cancer Database (NCDB). Methods: The NCDB was queried for patients with non-metastatic uterine sarcoma diagnosed between 2004 and 2018 treated with surgery. Uterine carcinosarcomas were excluded. Adjuvant patterns of care and temporal treatment trends were evaluated, stratified by histology. Multivariable logistic regression model was constructed to identify predictors of receipt of radiation. Results: Among 12, 806 patients, 88% received a total hysterectomy and bilateral salpingo- oophorectomy (TH-BSO) and 42% received lymph node sampling (LNS). Adjuvant patterns of care are reported in table 1 . The utilization of adjuvant chemotherapy in uterine sarcomas has increased over time from 10% in 2004 to 28% in 2018, while radiation therapy (RT) use has been decreasing from 25% in 2004 to 5% in 2018 ( figure 1, p< 0.05). This trend is particularly pronounced in leiomyosarcomas with utilization of RT decreasing from 27% to 3% and chemotherapy increasing from 14% to 33% from 2004 to 2018 (p<0.05). Predictors of receiving adjuvant RT varied by histology but included stage II or III, high grade, and >=7 lymph nodes removed. Conclusions: For uterine sarcomas, TH+BSO without LNS was the main surgical modality. We identified high-risk features predictive of receiving RT, including stage II/III, high grade, and more extensive LNS. Overall, adjuvant RT utilization is decreasing over time for uterine sarcomas, particularly in leiomyosarcomas.